Experimenting usage of camera-traps for population dynamics study of the Asian elephant Elephas maximus in southern India - Varma, Surendra; Pittet, André; Jamadagni, H. S. (Current science (Bangalore), 2006)
To evaluate the application of camera-trap technology in population dynamics studies of the Asian elephant, indigenously designed, cost-effective, infrared-triggered camera-traps were used. Usability of pictures was defined based on quality, clarity and positioning of the subject. With 99 pictures of 330 elephants, 20 sequences were obtained and 44 distinct individuals were identified. It was found that 38.6% were adult females, 4.5% adult males, 13.6% sub-adult females, 6.8% sub-adult males, 20.4% juvenile females, while juvenile males were poorly represented (2%), and 13.6% were calves. These results were surprisingly identical with those of other systematic and long-term studies.